Novel ALD Chemistry Enabled Low-Temperature Synthesis of Lithium Fluoride Coatings for Durable Lithium Anodes - Chen, Lin; Chen, Kan-Sheng; Chen, Xinjie; Ramirez, Giovanni; Huang, Zhennan; Geise, Natalie R.; Steinrück, Hans-Georg; Fisher, Brandon L.; Shahbazian-Yassar, Reza; Toney, Michael F.; Hersam, Mark C.; Elam, Jeffrey W. (ACS Applied Materials & Interfaces)

Fluoroethylene Carbonate Induces Ordered Electrolyte Interface on Silicon and Sapphire Surfaces as Revealed by Sum Frequency Generation Vibrational Spectroscopy and X-ray Reflectivity - Horowitz, Yonatan; Steinrück, Hans-Georg; Han, Hui-Ling; Cao, Chuntian; Abate, Iwnetim Iwnetu; Tsao, Yuchi; Toney, Michael F.; Somorjai, Gabor A. (Nano Letters)

The nanoscale structure of the electrolyte–metal oxide interface - Steinrück, Hans-Georg; Cao, Chuntian; Tsao, Yuchi; Takacs, Christopher J.; Konovalov, Oleg; Vatamanu, Jenel; Borodin, Oleg; Toney, Michael F. (Energy & Environmental Science)
Combined experimental and theoretical insights into electrolyte–electrode interfaces relevant to lithium ion batteries.

Surface structure evolution in a homologous series of ionic liquids - Haddad, Julia; Pontoni, Diego; Murphy, Bridget M.; Festersen, Sven; Runge, Benjamin; Magnussen, Olaf M.; Steinrück, Hans-Georg; Reichert, Harald; Ocko, Benjamin M.; Deutsch, Moshe (Proceedings of the National Academy of Sciences)
Interfaces of room temperature ionic liquids (RTILs) are important for both applications and basic science and are therefore intensely studied. However, the evolution of their interface structure with the cation’s alkyl chain length n from Coulomb to van der Waals interaction domination has not yet been studied for even a single broad homologous RTIL series. We present here such a study of the liquid–air interface for n=2to 22 , using angstrom-resolution X-ray methods. For n<6 , a typical “simple liquid” monotonic surface-normal electron density profile ρe(z) is obtained, like those of water and organic solvents. For n>6 , increasingly more pronounced nanoscale self-segregation of the molecules’ charged moieties and apolar chains yields surface layering with alternating regions of headgroups and chains. The layering decays into the bulk over a few, to a few tens, of nanometers. The layering periods and decay lengths, their linear n dependence, and slopes are discussed within two models, one with partial-chain interdigitation and the other with liquid-like chains. No surface-parallel long-range order is found within the surface layer. For n=22 , a different surface phase is observed above melting. Our results also impact general liquid-phase issues like supramolecular self-aggregation and bulk–surface structure relations.

Unterscheidung von Kontexten für den Chemieunterricht - van Vorst, Helena; Fechner, Sabine; Sumfleth, Elke (Zeitschrift für Didaktik der Naturwissenschaften)

Mentale Modelle - Nitz, Sandra; Fechner, Sabine (Theorien in der naturwissenschaftsdidaktischen Forschung)

Concrete and abstract external respresentations in chemistry education - Akman, Perihan; Fechner, Sabine (Electronic Proceedings of the ESERA 2017 Conference. Research, Practice and Collaboration in Science Education, Part 1 (co-ed. Finlayson, O. & Roser, P.))

Identifiction of students‘ questions in context-based learning approaches - Schmitz, Lisa; Fechner, Sabine (Electronic Proceedings of the ESERA 2017 Conference. Research, Practice and Collaboration in Science Education, Part 2 (co-ed. Tytler, R. & Carvalho, G. S.))

Science teaching processes (part 3). In Finlayson, O. E., McLoughlin, E., Erduran, S., Childs, P. (Eds.), Electronic Proceedings of the ESERA 2017 Conference. Research, Practice and Collaboration in Science Education

A novel approach to enhance ACL injury prevention programs. - Gokeler, A; Seil, R; Kerkhoffs, G; Verhagen, E (J Exp Orthop)

Cross-education does not accelerate the rehabilitation of neuromuscular functions after ACL reconstruction: a randomized controlled clinical trial. - Zult, T; Gokeler, A; Raay JJAM, van; Brouwer, RW; Zijdewind, I; Farthing, JP; Hortobágyi, T (Eur J Appl Physiol)

Angle-specific analysis of isokinetic quadriceps and hamstring torques and ratios in patients after ACL-reconstruction. - Baumgart, C; Welling, W; Hoppe, MW; Freiwald, J; Gokeler, A (BMC Sports Sci Med Rehabil)

Transfer of improved movement technique after receiving verbal external focus and video instruction. - Benjaminse, A; Welling, W; Otten, B; Gokeler, A (Knee Surg Sports Traumatol Arthrosc)

The effect of load on Achilles tendon structure in novice runners. - Heyward, OW; Rabello, LM; van der Woude, L; van den Akker-Scheek, I; Gokeler, A; van der Worp, H; Zwerver, J (J Sci Med Sport)

Let us rethink research for ACL injuries: a call for a more complex scientific approach. - Gokeler, A; Verhagen, E; Hirschmann, MT (Knee Surg Sports Traumatol Arthrosc)

The Relationship between Sensory Responses to Ankle Joint Loading and Corticomotor Excitability - Needle, AR; Baumeister, Jochen; Farquahr, WB; Greaney, JL; Higginson, JL; Kaminski, TW; Swanik, CB (Int J Neuroscience)

Low rates of patients meeting return to sport criteria 9 months after anterior cruciate ligament reconstruction: a prospective longitudinal study - Welling, W; Benjaminse, A; Seil, R; Lemmink, K; Zaffagnini, S; Gokeler, A (Knee Surg Sports Traumatol Arthrosc)

Nonoperative treatment of muscle injuries - recommendations from the GOTS expert meeting - Hotfiel, T; Seil, R; Bily, W; Bloch, W; Gokeler, A; Krifter, RM; Mayer, F; Ueblacker, P; Weisskopf, L; Engelhardt, M (J Exp Orthop)

Altered movement during single leg hop test after ACL reconstruction: implications to incorporate 2-D video movement analysis for hop test - Welling, W; Benjaminse, A; Seil, R; Lemmink, K; Gokeler, A (Knee Surg Sports Traumatol Arthrosc)

Comparison of postural stability in the ACL deficient and reconstructed leg: a Meta analysis - Lehmann, T; Paschen, Linda; Baumeister, Jochen

Negative emotional stimuli increase neurocognitive processing in the brain - An, YW; DiTrani Lobacz, A; Baumeister, Jochen; Swanik, CB

Exploring Functional Brain Connectivity of Postural Control in Upright Stance - Lehmann, T; Büchel, D; Cockcroft, J; Louw, QA; Baumeister, Jochen (Proceedings of the 3rd International Mobile Brain/Body Imaging Conference)

Effect of a cognitive dual-task on electrocortical activation during single leg stance - Büchel, D; Lehmann, T; Cockcroft, J; Louw, QA; Baumeister, Jochen (Proceedings of the 3rd International Mobile Brain/Body Imaging Conference)

Exact formulation of the transverse dynamic spin susceptibility as an initial-value problem - Schindlmayr, Arno (Advances in Mathematical Physics)
The transverse dynamic spin susceptibility is a correlation function that yields exact information about spin excitations in systems with a collinear magnetic ground state, including collective spin-wave modes. In an ab initio context, it may be calculated within many-body perturbation theory or time-dependent density-functional theory, but the quantitative accuracy is currently limited by the available functionals for exchange and correlation in dynamically evolving systems. To circumvent this limitation, the spin susceptibility is here alternatively formulated as the solution of an initial-value problem. In this way, the challenge of accurately describing exchange and correlation in many-electron systems is shifted to the stationary initial state, which is much better understood. The proposed scheme further requires the choice of an auxiliary basis set, which determines the speed of convergence but always allows systematic convergence in practical implementations.

Dynamics of DNA Origami Lattice Formation at Solid–Liquid Interfaces - Kielar, Charlotte; Ramakrishnan, Saminathan; Fricke, Sebastian; Grundmeier, Guido; Keller, Adrian (ACS Applied Materials & Interfaces)

Structural stability of DNA origami nanostructures under application-specific conditions - Ramakrishnan, Saminathan; Ijäs, Heini; Linko, Veikko; Keller, Adrian (Computational and Structural Biotechnology Journal)

Pharmacophore Nanoarrays on DNA Origami Substrates as a Single-Molecule Assay for Fragment-Based Drug Discovery - Kielar, Charlotte; Reddavide, Francesco V.; Tubbenhauer, Stefan; Cui, Meiying; Xu, Xiaodan; Grundmeier, Guido; Zhang, Yixin; Keller, Adrian (Angewandte Chemie International Edition)

Superstructure-Dependent Loading of DNA Origami Nanostructures with a Groove-Binding Drug - Kollmann, Fabian; Ramakrishnan, Saminathan; Shen, Boxuan; Grundmeier, Guido; Kostiainen, Mauri A.; Linko, Veikko; Keller, Adrian (ACS Omega)

Directed Protein Adsorption Through DNA Origami Masks - Ramakrishnan, Saminathan; Grundmeier, Guido; Keller, Adrian (DNA Nanotechnology: Methods and Protocols)

On the Stability of DNA Origami Nanostructures in Low-Magnesium Buffers - Kielar, Charlotte; Xin, Yang; Shen, Boxuan; Kostiainen, Mauri A.; Grundmeier, Guido; Linko, Veikko; Keller, Adrian (Angewandte Chemie International Edition)

On the Adsorption of DNA Origami Nanostructures in Nanohole Arrays - Brassat, Katharina; Ramakrishnan, Saminathan; Bürger, Julius; Hanke, Marcel; Doostdar, Mahnaz; Lindner, Jörg; Grundmeier, Guido; Keller, Adrian (Langmuir)

Ultrasound-mediated deposition and cytocompatibility of apatite-like coatings on magnesium alloys - Liu, Chen-Ni; Böke, Frederik; Gebhard, Maximilian; Devi, Anjana; Fischer, Horst; Keller, Adrian; Grundmeier, Guido (Surface and Coatings Technology)

Adsorption and Fibrillization of Islet Amyloid Polypeptide at Self-Assembled Monolayers Studied by QCM-D, AFM, and PM-IRRAS - Hajiraissi, Roozbeh; Hanke, Marcel; Yang, Yu; Duderija, Belma; Gonzalez Orive, Alejandro; Grundmeier, Guido; Keller, Adrian (Langmuir)

Multichannel vectorial holographic display and encryption - Zhao, Ruizhe; Sain, Basudeb; Wei, Qunshuo; Tang, Chengchun; Li, Xiaowei; Weiss, Thomas; Huang, Lingling; Wang, Yongtian; Zentgraf, Thomas (Light: Science & Applications)

Multilamellar Vesicle Formation Probed by Rheo-NMR and Rheo-SALS under Large Amplitude Oscillatory Shear - Kuczera, Stefan; Gentile, Luigi; Brox, Timothy I.; Olsson, Ulf; Schmidt, Claudia; Galvosas, Petrik (Langmuir)

Photonic crystal properties of Si and SiO2 nanopillar arrays fabricated by nanosphere lithography and metal-assisted wet-chemical etching - Kismann, Michael; Riedl, Thomas; Wu, Xia; Wagner, Thorsten; Lindner, Jörg

Strain Relaxation in InAs Nanoislands on top of GaAs (111) A Nanopillars - Riedl, Thomas; Kunnathully, Vinay; Trapp, Alexander; Reuter, Dirk; Lindner, Jörg

MBE Growth of InAs on Nanopillar-Patterned GaAs (111) A - Riedl, Thomas; Kunnathully, Vinay; Trapp, Alexander; Reuter, Dirk; Lindner, Jörg

Impact of shell growth on recombination dynamics and exciton-phonon interaction in CdSe-CdS core-shell nanoplatelets - Achtstein, Alexander W.; Marquardt, Oliver; Scott, Riccardo; Ibrahim, Mohamed; Riedl, Thomas; Prudnikau, Anatol V.; Antanovich, Artsiom; Owschimikow, Nina; Lindner, Jörg; Artemyev, Mikhail; Woggon, Ulrike (accepted 05.09.2018)

Self-assembled Surface Patterns for Controlled Nanoparticle Placement and Improved Semiconductor Heteroepitaxy - Brassat, Katharina; Riedl, Thomas; Lindner, Jörg

Exciton-Phonon Interaction in Core-Only, Core-Shell Nanoplatelets and Quantum Dots - Scott, Riccardo; Prudnikau, Anatol; Antanovich, Artsiom; Christodoulou, Soririos; Riedl, Thomas; Bertrand, Guilaume; Owschimikow, Nina; Lindner, Jörg; Hens, Zeger; Moreels, Iwan; Artemyev, Mikhail; Woggon, Ulrike; et al. (submitted to Nano Letters)

Stability of Heteroepitaxial Coherent Growth Modes on Nanowire Radial Surfaces - Riedl, Thomas; Lindner, Jörg (submitted to Phys. Rev. Mat.)

Modification of block copolymer lithography masks by O2 plasma treatment: Insights from lift off experiments, nanopore etching and free membranes - Brassat, Katharina; Kool, Daniel; Lindner, Jörg (To be submitted)

Nanostructure Research using Transmission Electron Microscopy at the new OWL Analytic Centre - Riedl, Thomas; Bürger, Julius; Kunnathully, Vinay; Wiegand, Marie; Duschik, K.; Ramermann, D.; Ennen, I.; Hertle, Y.; Schaper, Mirko; Hellweg, T.; Hütten, A.; Lindner, Jörg

State-of-the-art transmission electron microscopy in the imaging and scanning mode - Lindner, Jörg

Decay and revival of electron spin polarization in an ensemble of (In,Ga)As quantum dots - Evers, E.; Belykh, V. V.; Kopteva, N. E.; Yugova, I. A.; Greilich, A.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Interlayer charge transfer in n-modulation doped Al1−x Ga x As–GaAs single heterostructures - Schuster, J; Kim, T Y; Batke, E; Reuter, Dirk; Wieck, A D (Semiconductor Science and Technology)

Basic Requirements of Spin-Flip Raman Scattering on Excitonic Resonances and Its Modulation through Additional High-Energy Illumination in Semiconductor Heterostructures - Debus, J.; Kudlacik, D.; Sapega, V. F.; Shamirzaev, T. S.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Waag, A.; Bayer, M. (Physics of the Solid State)

Formation of self-assembled GaAs quantum dots via droplet epitaxy on misoriented GaAs(111)B substrates - Trapp, Alexander; Reuter, Dirk (Journal of Vacuum Science & Technology B, Nanotechnology and Microelectronics: Materials, Processing, Measurement, and Phenomena)

Site-controlled droplet epitaxy of GaAs quantum dots by deposition through shadow masks - Zolatanosha, Viktoryia; Reuter, Dirk (Journal of Vacuum Science & Technology B, Nanotechnology and Microelectronics: Materials, Processing, Measurement, and Phenomena)

Spin inertia of resident and photoexcited carriers in singly charged quantum dots - Zhukov, E. A.; Kirstein, E.; Smirnov, D. S.; Yakovlev, D. R.; Glazov, M. M.; Reuter, Dirk; Wieck, A. D.; Bayer, M.; Greilich, A. (Physical Review B)

Optical Properties of Cubic GaN Quantum Dots Grown by Molecular Beam Epitaxy - Blumenthal, Sarah; Reuter, Dirk; As, Donat Josef (physica status solidi (b))

Nonlinear Quasi-Phase Matching with metasurfaces - Heron, S.; Reineke, B.; Vezian, S.; Zentgraf, Thomas; Damilano, B.; Genevet, P. (2018 12th International Congress on Artificial Materials for Novel Wave Phenomena (Metamaterials))

Near-field plasmonic beam engineering by complex amplitude modulation based on metasurface (Conference Presentation) - Sun, Lin; Zhang, Xiaomeng; Zhao, Ruizhe; Li, Xiaowei; Wang, Jia; Bai, Benfeng; Wang, Yongtian; Zentgraf, Thomas; Huang, Lingling; Song, Xu (Nanophotonics VII)

Engineering integrated sources of entangled photon pairs - Meyer-Scott, Evan; Prasannan, Nidhin; Montaut, Nicola; Tiedau, Johannes; Harder, Georg; Sansoni, Linda; Herrmann, Harald; Eigner, Christof; Ricken, Raimund; Quiring, Viktor; Bartley, Tim; Barkhofen, Sonja; et al. (Frontiers in Optics / Laser Science)

Engineering integrated sources of entangled photon pairs - Meyer-Scott, Evan; Prasannan, Nidhin; Montaut, Nicola; Tiedau, Johannes; Harder, Georg; Sansoni, Linda; Herrmann, Harald; Eigner, Christof; Ricken, Raimund; Quiring, Viktor; Bartley, Tim J.; Barkhofen, Sonja; et al. (Frontiers in Optics / Laser Science)

Incomplete Detection of Nonclassical Phase-Space Distributions - Bohmann, M.; Tiedau, J.; Bartley, Tim; Sperling, J.; Silberhorn, C.; Vogel, W. (Physical Review Letters)

Hierarchical nanopores formed by block copolymer lithography on the surfaces of different materials pre-patterned by nanosphere lithography - Brassat, Katharina; Kool, Daniel; Bürger, Julius; Lindner, Jörg (Nanoscale)
Bottom-up patterning techniques allow for the creation of surfaces with ordered arrays of nanoscale features on large areas. Two bottom-up techniques suitable for the formation of regular nanopatterns on different length scales are nanosphere lithography (NSL) and block copolymer (BCP) lithography. In this paper it is shown that NSL and BCP lithography can be combined to easily design hierarchically nanopatterned surfaces of different materials. Nanosphere lithography is used for the pre-patterning of surfaces with antidots, i.e. hexagonally arranged cylindrical holes in thin films of Au, Pt and TiO2 on SiO2, providing a periodic chemical and topographical contrast on the surface suitable for templating in subsequent BCP lithography. PS-b-PMMA BCP is used in the second self-assembly step to form hexagonally arranged nanopores with sub-20 nm diameter within the antidots upon microphase separation. To achieve this the microphase separation of BCP on planar surfaces is studied, too, and it is demonstrated for the first time that vertical BCP nanopores can be formed on TiO2, Au and Pt films without using any neutralization layers. To explain this the influence of surface energy, polarity and roughness on the microphase separation is investigated and discussed along with the wetting state of BCP on NSL-pre-patterned surfaces. The presented novel route for the creation of advanced hierarchical nanopatterns is easily applicable on large-area surfaces of different materials. This flexibility makes it suitable for a broad range of applications, from the morphological design of biocompatible surfaces for life science to complex pre-patterns for nanoparticle placement in semiconductor technology.

A Novel Lubricant Based on Covalent Functionalized Graphene Oxide Quantum Dots - Wolk, Andreas; Rosenthal, Marta; Neuhaus, Stephan; Huber, Klaus; Brassat, Katharina; Lindner, Jörg; Grothe, Richard; Grundmeier, Guido; Bremser, Wolfgang; Wilhelm, René (Scientific Reports)
Dodecyl amine edge functionalized few-layer graphene oxide quantum dots were synthesized in good yields. The covalent functionalization was demonstrated with NMR and AFM-IR. The resulting structure and particle size was measured with AFM and HRTEM. The thermal stability of the compound was investigated and showed a stability of up to 220 °C. The modified graphene oxide quantum dots showed excellent solubility in various organic solvents, including ethers, methanol, toluene, n-hexane, heptane, xylene, dichloromethane and toluene. The stability of a resulting toluene solution was also proven by static light scattering measurements over several days. The excellent solubility gives the possibility of an efficient and fast spray application of the functionalized graphene oxide quantum dots to steel surfaces. Hence, the macroscopic friction behavior was investigated with a Thwing-Albert FP-2250 friction tester. A thin film of the dodecyl amine functionalized graphene oxide quantum dots on steel lowered the friction coefficient from 0.17 to 0.11 and revealed a significant corrosion inhibition effect.

Easily Accessible Protein Nanostructures via Enzyme Mediated Addressing - Rüdiger, Arne A.; Brassat, Katharina; Lindner, Jörg; Bremser, Wolfgang; Strube, Oliver I. (Langmuir)
Site-specific formation of nanoscaled protein structures is a challenging task. Most known structuring methods are either complex and hardly upscalable or do not apply to biological matter at all. The presented combination of enzyme mediated autodeposition and nanosphere lithography provides an easy-to-apply approach for the buildup of protein nanostructures over a large scale. The key factor is the tethering of enzyme to the support in designated areas. Those areas are provided via prepatterning of enzymatically active antidots with variable diameters. Enzymatically triggered protein addressing occurs exclusively at the intended areas and continues until the entire active area is coated. After this, the reaction self-terminates. The major advantage of the presented method lies in its easy applicability and upscalability. Large area structuring of entire support surfaces with features on the nanometer scale is performed efficiently and without the necessity of harsh conditions. These are valuable premises for large-scale applications with potentials in biosensor technology, nanoelectronics, and life sciences.

With directed self-arrangement of DNA origami to large-area quantum dot arrays - Grundmeier, Guido; Brassat, Katharina; Keller, A.; Lindner, Jörg

Hierarchical nanopore and nanoring arrays by self-assembly techniques - Brassat, Katharina; Kool, Daniel; Lindner, Jörg

Ti-6Al-4V alloy: 3D printing of lightweight implants and nanopatterning by self-assembly - Brassat, Katharina; Taube, A.; Kool, Daniel; Tasche, L.; Hoyer, K.P.; Schaper, Mirko; Lindner, Jörg

Morphology investigation of nanopores by block copolymer lithography on different material surfaces - Brassat, Katharina; Kool, Daniel; Taube, A.; Schaper, Mirko; Lindner, Jörg

Nanoscopic protein arrays on BCP prepatterned surfaces - Brassat, Katharina; Brüngeler, A.; Bremser, W.; Strube, O.I.; Lindner, Jörg

Hierarchical nanopatterns by site-selective DNA origami adsoprtion on pre-patterned surfaces - Brassat, Katharina; Ramakrishna, S.; Keller, A.; Lindner, Jörg

Simulation of Transport Processes during the Convective Self-Assembly of Colloidal Nanomasks - Drude, Dennis; Lindner, Jörg

Protein and DNA origami arrays on large areas by directed self-assembly - Brassat, Katharina; Bremser, W.; Strube, O.; Grundmeier, G.; Keller, A.; Lindner, Jörg

Selbstorganisation für die Nanotechnik von morgen - Lindner, Jörg

Nanoscale materials and interface design by self-organization - Lindner, Jörg

Third Harmonic Generation Enhanced by Multipolar Interference in Complementary Silicon Metasurfaces - Chen, Shumei; Rahmani, Mohsen; Li, King Fai; Miroshnichenko, Andrey; Zentgraf, Thomas; Li, Guixin; Neshev, Dragomir; Zhang, Shuang (ACS Photonics)

Spin and Geometric Phase Control Four-Wave Mixing from Metasurfaces - Li, Guixin; Sartorello, Giovanni; Chen, Shumei; Nicholls, Luke H.; Li, King Fai; Zentgraf, Thomas; Zhang, Shuang; Zayats, Anatoly V. (Laser & Photonics Reviews)

Editorial for the theories and applications of metasurfaces - Guo, Zhongyi; Chen, Xianzhong; Zentgraf, Thomas (Journal of Physics D: Applied Physics)

Controlling the phase of optical nonlinearity with plasmonic metasurfaces - Chen, Shumei; Li, Guixin; Cheah, Kok Wai; Zentgraf, Thomas; Zhang, Shuang (Nanophotonics)

Nanoscale Polarization Manipulation and Encryption Based on Dielectric Metasurfaces - Zhao, Ruizhe; Huang, Lingling; Tang, Chengchun; Li, Junjie; Li, Xiaowei; Wang, Yongtian; Zentgraf, Thomas (Advanced Optical Materials)

Exergames Inherently Contain Cognitive Elements as Indicated by Cortical Processing - Anders, Phillipp; Lehmann, Tim; Müller, Helen; Grønvik, Karoline B.; Skjæret-Maroni, Nina; Baumeister, Jochen; Vereijken, Beatrix (Frontiers in Behavioral Neuroscience)

Heralded orthogonalisation of coherent states and their conversion to discrete-variable superpositions - Kruse, Regina; Silberhorn, Christine; Bartley, Tim (Quantum Measurements and Quantum Metrology)
Abstract The nonorthogonality of coherent states is a fundamental property which prevents them from being perfectly and deterministically discriminated. Here, we present an experimentally feasible protocol for the probabilistic orthogonalisation of a pair of coherent states, independent of their amplitude and phase. In contrast to unambiguous state discrimination, a successful operation of our protocol is heralded without measuring the states. As such, they remain suitable for further manipulation and the obtained orthogonal states serve as a discretevariable basis. Therefore, our protocol doubles as a simple continuous-to-discrete variable converter, which may find application in hybrid continuous-discrete quantum information processing protocols.

The Bonding Situation in the Dinuclear Tetra-Hydrido Complex [{5CpFe}2(μ-H)4] Revisited by Hard X-Ray Spectroscopy - Burkhardt, Lukas; Mueller, Carsten; Groß, Oliver A.; Sun, Yu; Sitzmann, Helmut; Bauer, Matthias (Inorganic Chemistry)

Towards Noble-Metal-Free Dyads: Ground and Excited State Tuning by a Cobalt Dimethylglyoxime Motif Connected to an Iron N-Heterocyclic Carbene Photosensitizer - Zimmer, Peter; Burkhardt, Lukas; Schepper, Rahel; Zheng, Kaibo; Gosztola, David; Neuba, Adam; Flörke, Ulrich; Wölper, Christoph; Schoch, Roland; Gawelda, Wojciech; Canton, Sophie E.; Bauer, Matthias (European Journal of Inorganic Chemistry)

Eisenbasierte Photosensitizer für die Photokatalyse / vorgelegt von Dipl.-Chem. Peter Zimmer ; [Prof. Dr. Thomas Kühne (Vorsitz), Prof. Dr. Matthias Bauer (Erstgutachter), Jun.-Prof. Dr. Stephan Hohloch (Zweitgutachter), Priv.-Doz. Dr. Hans Egold] - Zimmer, Peter

High energy resolution X-ray absorption and emission based studies on the mononuclear spin crossover complex [Fe(L-N4Bn2)(NCS)2] / vorgelegt von Dipl.-Chem. Rahel Schepper ; [Prof. Dr.-Ing. Hans-Joachim Warnecke (Kommissionsvorsitz), Prof. Dr. Matthias Bauer (Erstgutachter), Jun.-Prof. Dr. Stephan Hohloch (Zweitgutachter), Prof. Dr. Thomas Kühne (Drittprüfer)] - Schepper, Rahel

Exotic complexes in one-dimensional Bose-Einstein condensates with spin-orbit coupling - Belobo, D. Belobo; Meier, T. (Scientific Reports)

Tailored UV Emission by Nonlinear IR Excitation from ZnO Photonic Crystal Nanocavities - Hoffmann, Sandro P.; Albert, Maximilian; Weber, Nils; Sievers, Denis; Förstner, Jens; Zentgraf, Thomas; Meier, Cedrik (ACS Photonics)
Keywords: tet_topic_phc

Efficient frequency conversion by combined photonic–plasmonic mode coupling - Weber, N.; Hoffmann, S. P.; Albert, M.; Zentgraf, Thomas; Meier, Cedrik (Journal of Applied Physics)

Structural dynamics upon photoexcitation-induced charge transfer in a dicopper(i)–disulfide complex - Naumova, Maria; Khakhulin, Dmitry; Rebarz, Mateusz; Rohrmüller, Martin; Dicke, Benjamin; Biednov, Mykola; Britz, Alexander; Espinoza, Shirly; Grimm-Lebsanft, Benjamin; Kloz, Miroslav; Kretzschmar, Norman; Neuba, Adam; et al. (Physical Chemistry Chemical Physics)
A study of structural evolution upon photoinduced charge transfer in a dicopper complex with biologically relevant sulfur coordination.

Probing quasi-one-dimensional band structures by plasmon spectroscopy - Lichtenstein, T.; Mamiyev, Z.; Braun, C.; Sanna, S.; Schmidt, Wolf Gero; Tegenkamp, C.; Pfnür, H. (Physical Review B)

Calculation of spin-spin zero-field splitting within periodic boundary conditions: Towards all-electron accuracy - Biktagirov, Timur; Schmidt, Wolf Gero; Gerstmann, Uwe (Physical Review B)

Erratum: Optical properties of titanium-doped lithium niobate from time-dependent density-functional theory [Phys. Rev. Materials 1, 034401 (2017)] - Friedrich, Michael; Schmidt, Wolf Gero; Schindlmayr, Arno; Sanna, Simone (Physical Review Materials)

Vibrational properties of the Au-(3×3)/Si(111) surface reconstruction - Halbig, B.; Liebhaber, M.; Bass, U.; Geurts, J.; Speiser, E.; Räthel, J.; Chandola, S.; Esser, N.; Krenz, Marvin; Neufeld, Sergej; Schmidt, Wolf Gero; Sanna, S. (Physical Review B)

Temperature stabilizes rough Au/Ge(001) surface reconstructions - Seino, Kaori; Sanna, Simone; Schmidt, Wolf Gero (Surface Science)

Probing quasi-one-dimensional band structures by plasmon spectroscopy - Lichtenstein, T.; Mamiyev, Z.; Braun, Christian; Sanna, S.; Schmidt, Wolf Gero; Tegenkamp, C.; Pfnür, H. (Physical Review B)

Beyond the molecular movie: Dynamics of bands and bonds during a photoinduced phase transition - Nicholson, C. W.; Lücke, A.; Schmidt, Wolf Gero; Puppin, M.; Rettig, L.; Ernstorfer, R.; Wolf, M. (Science)
Ultrafast nonequilibrium dynamics offer a route to study the microscopic interactions that govern macroscopic behavior. In particular, photoinduced phase transitions (PIPTs) in solids provide a test case for how forces, and the resulting atomic motion along a reaction coordinate, originate from a nonequilibrium population of excited electronic states. Using femtosecond photoemission, we obtain access to the transient electronic structure during an ultrafast PIPT in a model system: indium nanowires on a silicon(111) surface. We uncover a detailed reaction pathway, allowing a direct comparison with the dynamics predicted by ab initio simulations. This further reveals the crucial role played by localized photoholes in shaping the potential energy landscape and enables a combined momentum- and real-space description of PIPTs, including the ultrafast formation of chemical bonds.

Unraveling the Oxidation and Spin State of Mn–Corrole through X-ray Spectroscopy and Quantum Chemical Analysis - Paszkiewicz, Mateusz; Biktagirov, Timur; Aldahhak, Hazem; Allegretti, Francesco; Rauls, Eva; Schöfberger, Wolfgang; Schmidt, Wolf Gero; Barth, Johannes V.; Gerstmann, Uwe; Klappenberger, Florian (The Journal of Physical Chemistry Letters)

Identifying On-Surface Site-Selective Chemical Conversions by Theory-Aided NEXAFS Spectroscopy: The Case of Free-Base Corroles on Ag(111) - Aldahhak, Hazem; Paszkiewicz, M.; Rauls, E.; Allegretti, F.; Tebi, S.; Papageorgiou, A. C.; Zhang, Y.-Q.; Zhang, L.; Lin, T.; Paintner, T.; Koch, R.; Schmidt, Wolf Gero; et al. (Chemistry - A European Journal)

Light-responsive nanoparticles based on new polycarbonate polymers as innovative drug delivery systems for photosensitizers in PDT - Anderski, Juliane; Mahlert, Laura; Sun, Jingjiang; Birnbaum, Wolfgang; Mulac, Dennis; Schreiber, Sebastian; Herrmann, Fabian; Kuckling, Dirk; Langer, Klaus (International Journal of Pharmaceutics)
Keywords: NanoparticlesLight-responsive polymersPhotodynamic therapyPoly(lactic-co-glycolic acid)Intestinal cancer

Vortex Multistability and Bessel Vortices in Polariton Condensates. - Ma, Xuekai; Schumacher, Stefan (Physical Review Letters)

Theoretical Investigation of Interaction of CuInSe2 Absorber Material with Oxygen, Hydrogen, and Water - Sahoo, Sudhir; Kormath Madam Raghupathy, Ramya; Kühne, Thomas; Mirhosseini, Hossein (J. Phys. Chem. C)
We performed ab initio calculations to study oxygen and hydrogen point defects in the CuInSe2 (CISe) solar-cell material. We found that H interstitial defects (when one H atom is surrounded by four Se atoms) and HCu (when a H atom is replacing a Cu atom) are the most stable defects. Whereas these H substitutional defects remain neutral, H interstitial defects act as donor defects and are detrimental to the cell performance. The incorporation of H2 into the CISe lattice, on the other hand, is harmless to the p-type conductivity. Oxygen atoms tend to either substitute Se atoms in the CISe lattice or form interstitial defects, though the formation of substitutional defects is more favorable. All oxygen point defects have high formation energies, which results in a low concentration of these defects in CISe. However, the presence of oxygen in the system leads to the formation of secondary phases such as In2O3 and InCuO2. In addition to the point defects, we studied the adsorption of H2O molecules on a defect-free surface and a surface with a (2VCu + InCu) defect using the ab initio thermodynamics technique. Our results indicate that the dissociative water adsorption on the CISe surface is energetically unfavorable. Furthermore, in order to obtain a water-free surface, the surface with defects has to be calcined at a higher temperature compared to the defect-free surface.

Database screening of ternary chalcogenides for p-type transparent conductors - Kormath Madam Raghupathy, Ramya; Wiebeler, Hendrik; Kühne, Thomas; Felser, Claudia; Mirhosseini, Hossein (Chemistry of Materials)
In this work, we investigated ternary chalcogenide semiconductors to identify promising p-type transparent conducting materials (TCMs). High-throughput calculations were employed to find the compounds that satisfies our screening criteria. Our screening strategy was based on the size of band gaps, the values of hole effective masses, and p-type dopability. Our search led to the identification of seven promising compounds (IrSbS, Ba2GeSe4, Ba2SiSe4, Ba(BSe3)2, VCu3S4, NbCu3Se4, and CuBS2) as potential TCM candidates. In addition, branch point energy and optical absorption spectra calculations support our findings. Our results open a new direction for the design and development of p-type TCMs.

Biomolecule Sensor Based on Azlactone‐Modified Hydrogel Films - Li, Jie; Yu, Xiaoqian; Herberg, Artjom; Kuckling, Dirk (Macromolecular Rapid Communications)
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry

Dietary Acid Load and Mental Health Outcomes in Children and Adolescents: Results from the GINIplus and LISA Birth Cohort Studies - Bühlmeier, Judith; Harris, Carla; Koletzko, Sibylle; Lehmann, Irina; Bauer, Carl-Peter; Schikowski, Tamara; von Berg, Andrea; Berdel, Dietrich; Heinrich, Joachim; Hebebrand, Johannes; Föcker, Manuel; Standl, Marie; et al. (Nutrients)